EXPERIENCE OF PROPHYLAXIS OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN WITH PNEUMOCOCCAL POLYSACCHARIDE VACCINE - A.A. Ruleva; A.L. Perova (Вопросы современной педиатрии, 2010)
Pneumococcal infection induces both severe invasive diseases and widespread non-invasive disorders of respiratory tract; it can cause recurrent acute respiratory infections (ARI) and their complications. Present article analyzes experience of treatment with pneumococcal polysaccharide vaccine Pneumo 23. Authors studied morbidity with ARI (according to medical documentation) during 6–12 months after vaccination in children 2–14 years old with different pathologies. The study showed high efficacy of vaccination in frequently ailing children and patients with allergic diseases.Key words: children, pneumococcal infection, vaccination, efficacy.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(6):105-109)